Preparation process and application of a high-performance flame-retardant, low-smoke, halogen-free polyolefin cable
Through the combination of modified polyethylene and halogen-free flame retardant, combined with the technical means of modifying inorganic fillers with compound epoxy coupling agent, the problems of insufficient flame retardant performance, unstable temperature resistance and rapid aging in mining environments are solved, and the preparation of high-performance flame retardant low-smoke halogen-free polyolefin cables are realized, which are suitable for high-temperature, long-distance, and large-capacity power supply scenarios.
Patent Information
- Application Number
- CN202410924828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-07-10
AI Technical Summary
Polyolefin cables face problems such as insufficient flame retardant performance, unstable temperature resistance, and rapid aging in mining environments, and are difficult to meet the needs of high temperature, long distance, and large capacity power supply scenarios.
The high-performance flame retardant low-smoke halogen-free polyolefin cable is adopted to improve the flame retardant, high temperature resistance and wear resistance of the cable by combining modified polyethylene and halogen-free flame retardant, and the inorganic filler is modified by compounding epoxy coupling agent to improve the mechanical properties and aging resistance of the cable.
It realizes the high flame retardancy, high and low temperature resistance, aging resistance and wear resistance of the cable. It is suitable for harsh environments such as mining, and improves the safety and service life of the cable.
Smart Images

Figure CN118919176B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable preparation, and in particular relates to a preparation process and application of a high-performance flame-retardant low-smoke halogen-free polyolefin cable. Background Art
[0002] A cable is an assembly of wires used to transmit power, signals or data. It is usually composed of one or more mutually insulated conductive cores and encapsulated in a sealed sheath. It can have a variety of structures and characteristics depending on the purpose and environment, such as: (1) Power cable: mainly used for the transmission and distribution of electrical energy, can be found in high-voltage and low-voltage power networks, including overhead lines, underground cables, etc.; (2) Control cable: used to transmit control signals and low-voltage power in industrial automation systems; (3) Communication cable: including coaxial cable, twisted pair cable and fiber optic cable, used for voice communication, Internet connection and other forms of data transmission; (4) Special environment cable: designed for specific environments, such as high temperature resistance, cold resistance, corrosion resistance, wear resistance, explosion-proof, waterproof, etc.; (5) Mining cable: specially designed for the mining industry, capable of operating in harsh environments such as humidity, dust and explosion hazards.
[0003] As one of the widely used wire and cable materials, polyolefin cables have many advantages such as excellent electrical properties, chemical corrosion resistance, light weight, flexibility and easy processing, but they also face some technical challenges and problems in practical applications, mainly including but not limited to the following aspects:
[0004] 1. Flame retardant properties:
[0005] Polyolefins are flammable. In order to meet fire safety requirements, special additives must be used to improve their flame retardant properties. Halogen-containing flame retardant cables will produce a large amount of toxic hydrogen halide gas (such as HCl, HF, etc.) when burning, which is extremely harmful to the environment and human health. Halogen-free flame retardants have become a trend. Adding flame retardants may affect other properties of the material.
[0006] 2. Temperature resistance level:
[0007] In the mining environment, the long-term working temperature of polyolefin materials is unstable. Low temperatures often cause the cable to become brittle, affecting its performance.
[0008] 3. Aging and lifespan:
[0009] After long-term use, polyolefin cables may age due to factors such as heat, light, and oxidation, affecting their insulation performance and service life. Therefore, the formula needs to be optimized to improve their aging resistance.
[0010] In order to meet the special use requirements of mining conditions, higher performance mining cable products need to be developed for high temperature, long distance, and large capacity power supply scenarios. Therefore, the research and development and selection of mining cables must fully consider the above issues and improve the safety, durability, and adaptability of cables through technological innovation and strict quality management. Summary of the invention
[0011] The purpose of the present invention is to provide a preparation process and application of a high-performance flame-retardant low-smoke halogen-free polyolefin cable. The prepared cable has good flame retardancy, solves the embrittlement and aging problems of polyolefin cable materials at low temperatures, improves wear resistance and mechanical properties, and is suitable for use in mining environments.
[0012] In order to achieve the above object, the present invention provides the following technical solutions:
[0013] A preparation process of a high-performance flame-retardant low-smoke halogen-free polyolefin cable, wherein the cable comprises, from inside to outside, a conductive core 1, an inner insulating layer 2, an outer insulating layer 3, an armor layer 4 and an outer protective layer 5, and the preparation process comprises the following steps:
[0014] (1) twisting and re-twisting a plurality of tinned copper wire bundles to obtain a conductive core 1;
[0015] (2) using a 70 mm extruder to extrude the polyolefin composite material onto the conductive core 1 at a steam pressure of 0.5-1 MPa to form an insulating layer 2;
[0016] (3) using an 80 mm extruder to extrude the polyolefin composite material onto the inner insulating layer 2 at a steam pressure of 0.5-1.0 MPa to form an outer insulating layer 3;
[0017] (4) using a steel wire armoring machine to perform steel wire armoring on the outer insulating layer 3 to obtain an armor layer 4;
[0018] (5) Under a steam pressure of 0.5-1.0 MPa, a 90 mm extruder is used to extrude the polyolefin composite material onto the armor layer 4 to form an outer protective layer 5, thereby obtaining a high-performance flame-retardant low-smoke halogen-free polyolefin cable;
[0019] The polyolefin composite material comprises the following raw materials: by weight: 50-60 parts of modified polyethylene, 10-20 parts of polyvinyl chloride resin, 15-25 parts of EVA resin, 5-15 parts of ABS resin, 1-5 parts of light calcium carbonate, 4-9 parts of molybdenum oxide, 1-5 parts of yttrium oxide, 3-7 parts of trioctyl trimellitate, 1-2 parts of stearic acid, 4-8 parts of epoxy soybean oil, 2-6 parts of dioctyl terephthalate, 1-4 parts of zinc stearate, 2-5 parts of antioxidant, 30-50 parts of halogen-free flame retardant, 1-3 parts of light stabilizer, 1-2 parts of cross-linking sensitizer and 10-15 parts of modified filler;
[0020] The preparation method of the modified filler is:
[0021] (1) mixing nano silicon dioxide, aluminum borate whiskers and nano barium titanate in a mass ratio of 1.4-1.8:1:0.3-0.7 to obtain a composite filler;
[0022] (2) Compounding a composite filler, a composite epoxy coupling agent, ethanol and water in a mass ratio of 1:0.04-0.06:6:4, reacting at 45-55° C. for 2-3 hours under stirring conditions, filtering and drying to obtain a modified filler.
[0023] Furthermore, the composite epoxy coupling agent is a compound of 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane in a mass ratio of 1:2.5-3:1.4-1.9.
[0024] 2-(3,4-Epoxycyclohexane)ethyltriethoxysilane, CAS: 10217-34-2; 3-(2,3-Epoxypropyloxypropyl)methyldiethoxysilane, CAS: 2897-60-1; 2-(3,4-Epoxycyclohexane)ethyltrimethoxysilane, CAS: 3388-04-3.
[0025] Aluminum borate whiskers, 300-500nm, Hubei Shineng Chemical Technology Co., Ltd.
[0026] Nano silicon dioxide, particle size 100-200nm. Beijing Dekedaojin Technology Co., Ltd.
[0027] Nano-barium titanate, particle size 50-100nm. Beijing Juguang Yingchuang Technology Co., Ltd.
[0028] Polyolefin composite materials are important components of cables and directly affect the performance of cables. The anti-aging ability of cables prepared by polyolefins on the market is poor. Under the aging test at 180°C and 168h, the absolute values of the change rates of tensile strength and elongation at break of most products are greater than 10%. The inventor added nano-silicon dioxide, aluminum borate whiskers and nano-barium titanate of a specific ratio to the polyethylene composite system in order to improve the high temperature resistance, but the effect is not ideal. The present invention improves the high temperature resistance of the cable by modifying the three inorganic fillers with a compounded epoxy coupling agent. The analysis shows that the modified inorganic filler has better dispersibility in the system and better compatibility with the other components. At the same time, the epoxy group of the organic end group of the epoxy coupling agent can react with the other components in the system to generate a more stable cured structure, and the formed cross-linked network is more dense, while maintaining or even improving the mechanical properties of the composite material. At the same time, the compounded epoxy coupling agent can form a higher quality interface bond, which can maximize the filling amount of the inorganic filler in the resin system, thereby improving the temperature resistance of the polyolefin composite material. The inventor unexpectedly discovered that the wear resistance of the polyolefin composite material was also improved under this condition. However, the inventor also found that the modified inorganic filler would affect the toughness of the polyolefin composite material at low temperatures, that is, it would cause the material to become brittle at low temperatures. It is speculated that this is due to the rigidity and strength of the modified filler itself, and that the freedom of movement of the polyolefin molecular chain may be limited after filling.
[0029] Furthermore, the preparation method of the modified polyethylene is: dissolving 5-10 parts by mass of maleic anhydride, 12-17 parts by mass of fumaric acid and 0.3-0.7 parts by mass of benzoyl peroxide in 40-50 parts by mass of acetone, and then adding 100 parts by mass of polyethylene and 0.07-0.1 parts by mass of propylthiouracil, and extruding and granulating with a twin-screw extruder to obtain the modified polyethylene.
[0030] Furthermore, the extrusion temperature of the twin-screw extruder is 160° C.-180° C., and the rotation speed is 30-40 r / min.
[0031] Furthermore, the polyethylene is a compound of medium-density polyethylene, low-density polyethylene and high-density polyethylene in a mass ratio of 2-2.5:1:0.3-0.6.
[0032] Medium density polyethylene, melt flow rate is 0.64g / 10min (ASTM D-1238). Korean SK, brand DX800.
[0033] Low density polyethylene, melt index 25g / 10min (190℃ / 2.16kg). Aladdin, item number P434349.
[0034] High density polyethylene, melt index 2.2g / 10min (190℃ / 2.16kg). Aladdin, item number P434351.
[0035] Polyvinyl chloride resin, average molecular weight Mw is 77000. Aladdin, product number P657058.
[0036] EVA resin, ethylene-vinyl acetate copolymer, vinyl acetate 26wt.%, melt index 4g / 10min. Aladdin, item number P301631.
[0037] ABS resin, melt flow rate is 6g / 10min. Brand: Chimei, Taiwan, China, grade: PA-777D.
[0038] Polyethylene is a crystalline polymer material, and its crystal structure becomes harder at low temperatures, while the mechanical properties of the amorphous region (amorphous state) decrease sharply at low temperatures. The present invention modifies polyethylene and matches an appropriate amount of polyvinyl chloride resin, EVA resin, and ABS resin to improve the embrittlement problem of polyolefin composite materials at low temperatures. Analysis is that under this condition, the modified polyethylene changes the original crystalline structure, reduces the stress concentration effect encountered during crack propagation, is conducive to absorbing and dispersing external energy, thereby improving the toughness of the material at low temperatures, and is irradiated by a high-energy radiation source at the same time, and is blended and modified with the remaining components to produce a cross-linking reaction between the molecular chains. Under this condition, the flexibility of the polymer molecular chain can be produced, and the molecular chain structure and crystallinity of the product formed under this ratio are conducive to improving the performance at low temperatures. The present invention uses medium-density polyethylene, low-density polyethylene and high-density polyethylene to improve tensile strength and elongation at break.
[0039] Furthermore, the halogen-free flame retardant is a compound of aluminum hydroxide and magnesium hydroxide in a mass ratio of 6-9:1.
[0040] Aluminum hydroxide, Zibo Yishengjia Aluminum Co., Ltd., brand AH-1. Magnesium hydroxide, Hangzhou Hengge Nanotechnology Co., Ltd., model: HN-MHT40U.
[0041] Furthermore, the antioxidant is 2,6-di-tert-butyl-4-methylphenol. CAS: 128-37-0.
[0042] Furthermore, the cross-linking sensitizer is triallyl isocyanurate. CAS: 1025-15-6.
[0043] Furthermore, the light stabilizer is UV absorber UV944. Changzhou Youfeng Chemical Co., Ltd.
[0044] Light calcium carbonate, Jiangxi Jingxue Calcium Carbonate Co., Ltd.
[0045] Epoxidized soybean oil, Shandong Zhouhe Chemical Co., Ltd.
[0046] Furthermore, the preparation method of the polyolefin composite material is: weighing raw materials according to the mass ratio, putting the raw materials into a mixer and mixing them at 160-170° C. for 40-50 minutes, then irradiating them with a high-energy electron beam with an irradiation energy of 175-180 kGy, and putting the irradiated mixture into a granulator for granulation to obtain the polyolefin composite material.
[0047] The invention provides application of a high-performance flame-retardant low-smoke halogen-free polyolefin cable prepared by the preparation process, and application of the cable in the mining industry.
[0048] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0049] 1. The present invention provides a preparation process and application of a high-performance flame-retardant low-smoke halogen-free polyolefin cable. The prepared cable has good flame retardancy, strong high and low temperature resistance, strong water resistance, good wear resistance, and excellent comprehensive performance, and is suitable for use in a mining environment.
[0050] 2. The present invention improves the high temperature resistance of the cable and the wear resistance of the polyolefin composite material by modifying the three inorganic fillers with a compounded epoxy coupling agent.
[0051] 3. The present invention modifies polyethylene and adds appropriate amounts of polyvinyl chloride resin, EVA resin, and ABS resin to improve the brittleness problem of polyolefin composite materials at low temperatures. The use of medium-density polyethylene, low-density polyethylene, and high-density polyethylene in combination improves tensile strength and elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a structural schematic diagram of a high-performance flame-retardant low-smoke halogen-free polyolefin cable;
[0053] In the figure, 1, conductive core; 2, inner insulating layer; 3, outer insulating layer; 4, armor layer; 5, outer protective layer 5. DETAILED DESCRIPTION
[0054] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] This embodiment provides a preparation process of a high-performance flame-retardant low-smoke halogen-free polyolefin cable, comprising a conductive core 1, an inner insulating layer 2, an outer insulating layer 3, an armor layer 4 and an outer protective layer 5, the preparation process comprising the following steps:
[0057] (1) twisting and re-twisting a plurality of tinned copper wire bundles to obtain a conductive core 1;
[0058] (2) Under a steam pressure of 1 MPa, a 70 mm extruder is used to extrude the polyolefin composite material onto the conductive core 1 to form an insulating layer 2;
[0059] (3) Under a steam pressure of 1.0 MPa, use an 80 mm extruder to extrude the polyolefin composite material onto the inner insulating layer 2 to form an outer insulating layer 3;
[0060] (4) using a steel wire armoring machine to perform steel wire armoring on the outer insulating layer 3 to obtain an armor layer 4;
[0061] (5) Under a steam pressure of 1.0 MPa, a 90 mm extruder is used to extrude the polyolefin composite material onto the armor layer 4 to form an outer protective layer 5, thereby obtaining a high-performance flame-retardant low-smoke halogen-free polyolefin cable;
[0062] The polyolefin composite material comprises the following raw materials: by weight: 54 parts of modified polyethylene, 16 parts of polyvinyl chloride resin, 21 parts of EVA resin, 11 parts of ABS resin, 3 parts of light calcium carbonate, 6 parts of molybdenum oxide, 4 parts of yttrium oxide, 5 parts of trioctyl trimellitate, 1.4 parts of stearic acid, 6 parts of epoxy soybean oil, 4 parts of dioctyl terephthalate, 2 parts of zinc stearate, 3 parts of antioxidant, 40 parts of halogen-free flame retardant, 2 parts of light stabilizer, 1.3 parts of cross-linking sensitizer and 13 parts of modified filler;
[0063] The preparation method of the modified filler is:
[0064] (1) mixing nano-silicon dioxide, aluminum borate whiskers and nano-barium titanate in a mass ratio of 1.6:1:0.5 to obtain a composite filler;
[0065] (2) The composite filler, composite epoxy coupling agent, ethanol and water were mixed in a mass ratio of 1:0.05:6:4, reacted at 50°C for 2.4 hours under stirring conditions, filtered and dried to obtain a modified filler.
[0066] The composite epoxy coupling agent is a compound of 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane in a mass ratio of 1:2.7:1.6.
[0067] Aluminum borate whiskers, 300-500nm, Hubei Shineng Chemical Technology Co., Ltd.
[0068] Nano silicon dioxide, particle size 100-200nm. Beijing Dekedaojin Technology Co., Ltd.
[0069] Nano-barium titanate, particle size 50-100nm. Beijing Juguang Yingchuang Technology Co., Ltd.
[0070] The preparation method of the modified polyethylene is as follows: 7 parts by mass of maleic anhydride, 15 parts by mass of fumaric acid and 0.5 parts by mass of benzoyl peroxide are dissolved in 45 parts by mass of acetone, 100 parts by mass of polyethylene and 0.08 parts by mass of propylthiouracil are added, and a twin-screw extruder is used for extrusion granulation to obtain the modified polyethylene.
[0071] The extrusion temperature of the twin-screw extruder is 170°C and the rotation speed is 40r / min.
[0072] The polyethylene is a compound of medium-density polyethylene, low-density polyethylene and high-density polyethylene in a mass ratio of 2.2:1:0.5.
[0073] Medium density polyethylene, melt flow rate is 0.64g / 10min (ASTM D-1238). Korean SK, brand DX800.
[0074] Low density polyethylene, melt index 25g / 10min (190℃ / 2.16kg). Aladdin, item number P434349.
[0075] High density polyethylene, melt index 2.2g / 10min (190℃ / 2.16kg). Aladdin, item number P434351.
[0076] Polyvinyl chloride resin, average molecular weight Mw is 77000. Aladdin, product number P657058.
[0077] EVA resin, ethylene-vinyl acetate copolymer, vinyl acetate 26wt.%, melt index 4g / 10min. Aladdin, item number P301631.
[0078] ABS resin, melt flow rate is 6g / 10min. Brand: Chimei, Taiwan, China, grade: PA-777D.
[0079] The halogen-free flame retardant is a compound of aluminum hydroxide and magnesium hydroxide in a mass ratio of 8:1.
[0080] Aluminum hydroxide, Zibo Yishengjia Aluminum Co., Ltd., brand AH-1. Magnesium hydroxide, Hangzhou Hengge Nanotechnology Co., Ltd., model: HN-MHT40U.
[0081] The antioxidant is 2,6-di-tert-butyl-4-methylphenol. CAS: 128-37-0.
[0082] The cross-linking sensitizer is triallyl isocyanurate. CAS: 1025-15-6.
[0083] The light stabilizer is UV absorber UV944. Changzhou Youfeng Chemical Co., Ltd.
[0084] Light calcium carbonate, Jiangxi Jingxue Calcium Carbonate Co., Ltd.
[0085] Epoxidized soybean oil, Shandong Zhouhe Chemical Co., Ltd.
[0086] The preparation method of the polyolefin composite material comprises: weighing raw materials according to the mass ratio, putting the raw materials into a mixer and mixing them at 165° C. for 45 minutes, then irradiating them with a high-energy electron beam with an irradiation energy of 180 kGy, and putting the irradiated mixture into a granulator for granulation to obtain the polyolefin composite material.
[0087] Example 2
[0088] This embodiment provides a preparation process of a high-performance flame-retardant low-smoke halogen-free polyolefin cable, comprising a conductive core 1, an inner insulating layer 2, an outer insulating layer 3, an armor layer 4 and an outer protective layer 5, the preparation process comprising the following steps:
[0089] (1) twisting and re-twisting a plurality of tinned copper wire bundles to obtain a conductive core 1;
[0090] (2) Under a steam pressure of 1 MPa, a 70 mm extruder is used to extrude the polyolefin composite material onto the conductive core 1 to form an insulating layer 2;
[0091] (3) Under a steam pressure of 1.0 MPa, use an 80 mm extruder to extrude the polyolefin composite material onto the inner insulating layer 2 to form an outer insulating layer 3;
[0092] (4) using a steel wire armoring machine to perform steel wire armoring on the outer insulating layer 3 to obtain an armor layer 4;
[0093] (5) Under a steam pressure of 1.0 MPa, a 90 mm extruder is used to extrude the polyolefin composite material onto the armor layer 4 to form an outer protective layer 5, thereby obtaining a high-performance flame-retardant low-smoke halogen-free polyolefin cable;
[0094] The polyolefin composite material comprises the following raw materials: by weight: 52 parts of modified polyethylene, 19 parts of polyvinyl chloride resin, 16 parts of EVA resin, 14 parts of ABS resin, 5 parts of light calcium carbonate, 4 parts of molybdenum oxide, 1 part of yttrium oxide, 7 parts of trioctyl trimellitate, 1 part of stearic acid, 8 parts of epoxy soybean oil, 2 parts of dioctyl terephthalate, 4 parts of zinc stearate, 2 parts of antioxidant, 48 parts of halogen-free flame retardant, 3 parts of light stabilizer, 1 part of cross-linking sensitizer and 15 parts of modified filler;
[0095] The preparation method of the modified filler is:
[0096] (1) mixing nano silicon dioxide, aluminum borate whiskers and nano barium titanate in a mass ratio of 1.4:1:0.7 to obtain a composite filler;
[0097] (2) The composite filler, composite epoxy coupling agent, ethanol and water were mixed in a mass ratio of 1:0.06:6:4, reacted at 45°C for 3 hours under stirring conditions, filtered and dried to obtain a modified filler.
[0098] The composite epoxy coupling agent is a compound of 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane in a mass ratio of 1:3:1.4.
[0099] Aluminum borate whiskers, 300-500nm, Hubei Shineng Chemical Technology Co., Ltd.
[0100] Nano silicon dioxide, particle size 100-200nm. Beijing Dekedaojin Technology Co., Ltd.
[0101] Nano-barium titanate, particle size 50-100nm. Beijing Juguang Yingchuang Technology Co., Ltd.
[0102] The preparation method of the modified polyethylene is as follows: 10 parts by mass of maleic anhydride, 12 parts by mass of fumaric acid and 0.7 parts by mass of benzoyl peroxide are dissolved in 40 parts by mass of acetone, 100 parts by mass of polyethylene and 0.1 parts by mass of propylthiouracil are added, and a twin-screw extruder is used for extrusion granulation to obtain the modified polyethylene.
[0103] The extrusion temperature of the twin-screw extruder is 180°C and the rotation speed is 30r / min.
[0104] The polyethylene is a compound of medium-density polyethylene, low-density polyethylene and high-density polyethylene in a mass ratio of 2:1:0.6.
[0105] Medium density polyethylene, melt flow rate is 0.64g / 10min (ASTM D-1238). Korean SK, brand DX800.
[0106] Low density polyethylene, melt index 25g / 10min (190℃ / 2.16kg). Aladdin, item number P434349.
[0107] High density polyethylene, melt index 2.2g / 10min (190℃ / 2.16kg). Aladdin, item number P434351.
[0108] Polyvinyl chloride resin, average molecular weight Mw is 77000. Aladdin, product number P657058.
[0109] EVA resin, ethylene-vinyl acetate copolymer, vinyl acetate 26wt.%, melt index 4g / 10min. Aladdin, item number P301631.
[0110] ABS resin, melt flow rate is 6g / 10min. Brand: Chimei, Taiwan, China, grade: PA-777D.
[0111] The halogen-free flame retardant is a compound of aluminum hydroxide and magnesium hydroxide in a mass ratio of 6:1.
[0112] Aluminum hydroxide, Zibo Yishengjia Aluminum Co., Ltd., brand AH-1. Magnesium hydroxide, Hangzhou Hengge Nanotechnology Co., Ltd., model: HN-MHT40U.
[0113] The antioxidant is 2,6-di-tert-butyl-4-methylphenol. CAS: 128-37-0.
[0114] The cross-linking sensitizer is triallyl isocyanurate. CAS: 1025-15-6.
[0115] The light stabilizer is UV absorber UV944. Changzhou Youfeng Chemical Co., Ltd.
[0116] Light calcium carbonate, Jiangxi Jingxue Calcium Carbonate Co., Ltd.
[0117] Epoxidized soybean oil, Shandong Zhouhe Chemical Co., Ltd.
[0118] The preparation method of the polyolefin composite material comprises: weighing raw materials according to the mass ratio, putting the raw materials into a mixer and mixing them at 170° C. for 40 minutes, then irradiating them with a high-energy electron beam with an irradiation energy of 175 kGy, and putting the irradiated mixture into a granulator for granulation to obtain the polyolefin composite material.
[0119] Comparative Example 1
[0120] The difference between this comparative example and Example 1 is that the raw material ratio of the polyolefin composite material is different.
[0121] The polyolefin composite material includes the following raw materials: by mass: 44 parts of modified polyethylene, 32 parts of polyvinyl chloride resin, 5 parts of EVA resin, 21 parts of ABS resin, 3 parts of light calcium carbonate, 6 parts of molybdenum oxide, 4 parts of yttrium oxide, 5 parts of trioctyl trimellitate, 1.4 parts of stearic acid, 6 parts of epoxy soybean oil, 4 parts of dioctyl terephthalate, 2 parts of zinc stearate, 3 parts of antioxidant, 40 parts of halogen-free flame retardant, 2 parts of light stabilizer, 1.3 parts of cross-linking sensitizer and 13 parts of modified filler.
[0122] Comparative Example 2
[0123] The difference between this comparative example and Example 1 is that the polyolefin is not modified.
[0124] The polyolefin composite material includes the following raw materials: by weight, 54 parts of polyethylene, 16 parts of polyvinyl chloride resin, 21 parts of EVA resin, 11 parts of ABS resin, 3 parts of light calcium carbonate, 6 parts of molybdenum oxide, 4 parts of yttrium oxide, 5 parts of trioctyl trimellitate, 1.4 parts of stearic acid, 6 parts of epoxy soybean oil, 4 parts of dioctyl terephthalate, 2 parts of zinc stearate, 3 parts of antioxidant, 40 parts of halogen-free flame retardant, 2 parts of light stabilizer, 1.3 parts of cross-linking sensitizer and 13 parts of modified filler.
[0125] Comparative Example 3
[0126] The difference between this comparative example and Example 1 is that the raw material composition of the polyolefin composite material is different.
[0127] The polyolefin composite material includes the following raw materials: by weight, 54 parts of modified polyethylene, 16 parts of epichlorohydrin rubber, 21 parts of chlorosulfonated polyethylene rubber, 11 parts of ABS resin, 3 parts of light calcium carbonate, 6 parts of molybdenum oxide, 4 parts of yttrium oxide, 5 parts of trioctyl trimellitate, 1.4 parts of stearic acid, 6 parts of epoxy soybean oil, 4 parts of dioctyl terephthalate, 2 parts of zinc stearate, 3 parts of antioxidant, 40 parts of halogen-free flame retardant, 2 parts of light stabilizer, 1.3 parts of cross-linking sensitizer and 13 parts of modified filler.
[0128] Chlorosulfonated polyethylene rubber, Wuhan Jiyesheng Chemical Co., Ltd.
[0129] Epichlorohydrin rubber, Hainan Xingshengfa Chemical Technology Co., Ltd.
[0130] Comparative Example 4
[0131] The difference between this comparative example and Example 1 is that the polyethylene is a compound of medium-density polyethylene, low-density polyethylene and high-density polyethylene in a mass ratio of 1:1:1.
[0132] Comparative Example 5
[0133] The difference between this comparative example and Example 1 is that the preparation method of the modified filler is: compounding aluminum borate whisker, composite epoxy coupling agent, ethanol and water in a mass ratio of 1:0.05:6:4, reacting at 50°C for 2.4 hours under stirring conditions, filtering and drying to obtain the modified filler.
[0134] The composite epoxy coupling agent is a compound of 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane in a mass ratio of 1:2.7:1.6.
[0135] Aluminum borate whiskers, 300-500nm, Hubei Shineng Chemical Technology Co., Ltd.
[0136] Comparative Example 6
[0137] The difference between this comparative example and Example 1 is that the preparation method of the modified filler is:
[0138] (1) mixing nano-silicon dioxide, aluminum borate whiskers and nano-barium titanate in a mass ratio of 1.6:1:0.5 to obtain a composite filler;
[0139] (2) The composite filler, silane coupling agent KH550, ethanol and water were mixed in a mass ratio of 1:0.05:6:4, reacted at 50°C for 2.4 hours under stirring conditions, filtered and dried to obtain a modified filler.
[0140] Comparative Example 7
[0141] The difference between this comparative example and Example 1 is that the proportions and particle sizes of nano-silicon dioxide, aluminum borate whiskers and nano-barium titanate are different.
[0142] The preparation method of the modified filler is:
[0143] (1) mixing nano silicon dioxide, aluminum borate whiskers and nano barium titanate in a mass ratio of 1:1:1 to obtain a composite filler;
[0144] (2) The composite filler, composite epoxy coupling agent, ethanol and water were mixed in a mass ratio of 1:0.05:6:4, reacted at 50°C for 2.4 hours under stirring conditions, filtered and dried to obtain a modified filler.
[0145] Aluminum borate whiskers, 700-900nm. Hubei Shineng Chemical Technology Co., Ltd.
[0146] Nano silicon dioxide, particle size 400-500nm. Beijing Dekedaojin Technology Co., Ltd.
[0147] Nano-barium titanate, particle size 200-300nm. Beijing Juguang Yingchuang Technology Co., Ltd.
[0148] Comparative Example 8
[0149] The difference between this comparative example and Example 1 is that the proportion of the composite epoxy coupling agent is different.
[0150] The composite epoxy coupling agent is a mixture of 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane in a mass ratio of 1:1:1.
[0151] Comparative Example 9
[0152] The difference between this comparative example and Example 1 is that the parameters of the polyvinyl chloride resin, the EVA resin and the ABS resin are different.
[0153] Polyvinyl chloride resin, average molecular weight Mw is 32000. Shandong Ketian Chemical Co., Ltd.
[0154] EVA resin, ethylene-vinyl acetate copolymer, vinyl acetate 19wt.%, melt index 4.8g / 10min. Aladdin, item number P301635.
[0155] ABS resin, melt flow rate is 2.2g / 10min. Korea Lotte AS-0150W.
[0156] Performance Testing
[0157] The performance tests were performed on the polyolefin composite materials of Examples 1-2 and Comparative Examples 1-9:
[0158] (1) Refer to GB / T 32129-2015 to test tensile strength and elongation at break;
[0159] (2) Refer to GB / T 5470-2008, -30℃, test low temperature embrittlement impact;
[0160] (3) Heat aging test according to GB / T 32129-2015, 180°C, 168h;
[0161] (4) Test the limiting oxygen index according to GB / T 2406.2-2009;
[0162] (5) Use the wire and cable scratch resistance tester (Shanghai Chengwei Instrument Technology Co., Ltd.) to test 0.5mm 2 Abrasion times of polyolefin composites.
[0163] Table 1 Performance test results
[0164]
[0165]
[0166] The results show that the polyolefin composite materials of Examples 1-2 have excellent comprehensive performance, can improve the performance of cables accordingly, and have stronger adaptability to the mining environment. Comparative Examples 1-9 show that the comprehensive performance decreases to varying degrees when the preparation conditions are changed.
[0167] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A process for preparing a high-performance flame-retardant low-smoke halogen-free polyolefin cable, characterized in that: The cable comprises, from the inside to the outside, a conductive core (1), an inner insulating layer (2), an outer insulating layer (3), an armor layer (4) and an outer protective layer (5), and the preparation process comprises the following steps: (1) twisting and re-twisting a plurality of tinned copper wire bundles to obtain a conductive core (1); (2) using an extruder to extrude the polyolefin composite material onto the conductive core (1) to form an inner insulating layer (2); (3) using an extruder to extrude the polyolefin composite material onto the inner insulating layer (2) to form an outer insulating layer (3); (4) using a steel wire armoring machine to perform steel wire armoring on the outer insulating layer (3) to obtain an armor layer (4); (5) using an extruder to extrude the polyolefin composite material onto the armor layer (4) to form an outer protective layer (5), thereby obtaining a high-performance flame-retardant low-smoke halogen-free polyolefin cable; The polyolefin composite material comprises the following raw materials: by weight: 50-60 parts of modified polyethylene, 10-20 parts of polyvinyl chloride resin, 15-25 parts of EVA resin, 5-15 parts of ABS resin, 1-5 parts of light calcium carbonate, 4-9 parts of molybdenum oxide, 1-5 parts of yttrium oxide, 3-7 parts of trioctyl trimellitate, 1-2 parts of stearic acid, 4-8 parts of epoxy soybean oil, 2-6 parts of dioctyl terephthalate, 1-4 parts of zinc stearate, 2-5 parts of antioxidant, 30-50 parts of halogen-free flame retardant, 1-3 parts of light stabilizer, 1-2 parts of cross-linking sensitizer and 10-15 parts of modified filler; The preparation method of the modified polyethylene is as follows: 5-10 parts by mass of maleic anhydride, 12-17 parts by mass of fumaric acid and 0.3-0.7 parts by mass of benzoyl peroxide are dissolved in 40-50 parts by mass of acetone, 100 parts by mass of polyethylene and 0.07-0.1 parts by mass of propylthiouracil are added, and a twin-screw extruder is used for extrusion granulation to obtain the modified polyethylene.
2. The preparation process of the high performance flame retardant low smoke halogen free polyolefin cable according to claim 1, characterized in that: The preparation method of the modified filler is: (1) Mixing nano-silicon dioxide, aluminum borate whiskers and nano-barium titanate in a mass ratio of 1.4-1.8:1:0.3-0.7 to obtain a composite filler; (2) Compounding a composite filler, a composite epoxy coupling agent, ethanol and water in a mass ratio of 1:0.04-0.06:6:4, reacting at 45-55°C for 2-3 hours under stirring conditions, filtering and drying to obtain a modified filler.
3. The preparation process of the high performance flame retardant low smoke zero halogen polyolefin cable according to claim 2, characterized in that: The composite epoxy coupling agent is a compound of 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane and 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane in a mass ratio of 1:2.5-3:1.4-1.
9.
4. The preparation process of the high performance flame retardant low smoke halogen free polyolefin cable according to claim 1, characterized in that: The extrusion temperature of the twin-screw extruder is 160℃-180℃, and the rotation speed is 30-40r / min.
5. The preparation process of the high performance flame retardant low smoke halogen free polyolefin cable according to claim 1, characterized in that: The polyethylene is a compound of medium-density polyethylene, low-density polyethylene and high-density polyethylene in a mass ratio of 2-2.5:1:0.3-0.
6.
6. The process for preparing a high performance flame retardant low smoke halogen free polyolefin cable according to claim 1, characterized in that: The halogen-free flame retardant is a compound of aluminum hydroxide and magnesium hydroxide in a mass ratio of 6-9:
1.
7. The process for preparing a high performance flame retardant low smoke halogen free polyolefin cable according to claim 1, characterized in that: The antioxidant is 2,6-di-tert-butyl-4-methylphenol; the cross-linking sensitizer is triallyl isocyanurate; and the light stabilizer is ultraviolet absorber UV944.
8. The process for preparing a high performance flame retardant low smoke halogen free polyolefin cable according to claim 1, characterized in that: The preparation method of the polyolefin composite material comprises: weighing raw materials according to mass ratio, putting the raw materials into a mixer and mixing them at 160-170° C. for 40-50 minutes, then irradiating them with high-energy electron beams with an irradiation energy of 175-180 kGy, and putting the irradiated mixture into a granulator for granulation to obtain the polyolefin composite material.
9. Use of a high-performance flame-retardant low-smoke halogen-free polyolefin cable prepared by the preparation process according to any one of claims 1 to 8, characterized in that: Application of the cable in the mining industry.
Citation Information
Patent Citations
Process for the continuous dyeing of threads and slivers of dry spun acrylonitrile polymers
CA1025156A
Oil-proof flame-retardant modified polyvinyl chloride cable sheathing material
CN103540064A
High-flame-retardation cable material for indoor optical fiber cord and preparation method
CN105837921A